How to Start Teaching Amharic Verbs? - Krzyżanowska, Magdalena (Aethiopica, 2019)
The Amharic verbal system—with its complexity in terms of form, meaning, and usage—poses a great challenge to both teacher and learner. Although the majority of Amharic textbooks give due consideration to the teaching of verbs, the activities that they offer only allow the student to get familiar with forms, in isolation from their meaning and context of use. The aim of this paper is to propose a way of introducing learners to the Amharic verbal system while focusing on form in communicative interactions. I argue that the system can be introduced, traditionally, with the perfective form, and in contexts involving meaningful communication. I also suggest a more student-centred (inductive) approach to presenting and explaining grammar in general and to the verbal system in particular. My discussion is illustrated by an exemplary unit from a course book that targets two perfective forms, third singular masculine and third singular feminine.